IDENTIFIKASI LAPISAN BAWAH TANAH DENGAN METODE GEOLISTRIK KONFIGURASI WENNER DI AREA WISATA AIR PANAS SUNGAI PINANG KABUPATEN KUANTAN SINGINGI - Rizza Naflah Herlinda; Usman Malik (Universitas Riau, 2023)
One of the geothermal prospecting areas in Riau is located in Sungai Pinang Village, Kuantan Singingi. Geothermal prospects in this village are characterized by the presence of geothermal manifestations on the surface in the form of hot springs. The purpose of this research is to analyze the rock lithology, the depth of the permeable layer, and the profile of hot springs. The method used is the geoelectric method with the Wenner Configuration. The results obtained in line 1 have a rock lithology of clay, sandstone, limestone, and andesite rocks with a permeable rock layer located at a depth of 1.25–15.9 meters.The results obtained in line 2 have rock lithologies of clay, gravel, and andesite with permeable rock layers located at a depth of 1.25 – 9.26 meters. The hot springs come from underground pressure that forces hot water to the surface through fractures to form geothermal manifestations on the surface.The hot springs found on both lines have resistivity values of 1.19–10 Ωm on line 1 and 0.524 – 9.69 Ωm on line 2.